From common language to common organization: Organization of Turkic states - YALÇINKAYA, ALAEDDİN (My University, 2022)
Following the collapse of the Soviet Union, the \"Summit of the Cooperation Council of Turkic Speaking States\", formed as a result of the 1992 Ankaraand 1993 Almaty agreements, became the \"Organization of Turkic States\" (TDT) following the 2021 Istanbul Summit. In the meantime, sub-units wereformed at stages such as Turksoy, Turkic Council, Turkic Kenesh, and documents were signed. Having started with the language, culture, andeducation and being the platform where economic goals have increasingly taken place, the distinctive feature of this organization is that it hastransformed into an organization that is based on peace and trust, cautious, and constantly developing. Undoubtedly, the basis of this success is thecommon history, culture, common interests, and then the need for solidarity, which are becoming more and more significant today.International organizations have an establishment process that matures through meetings such as summits and conferences. And the importantthing is how functional it is and how realistic its goals are. In this sense, there are many international organizations, some of which have beenforgotten in nursing homes or hospitals, and are not very active. Also, no matter how dysfunctional some of the organizations established on thebasis of regional or common identities, etc., the fact that even the representatives of the member states are able to come together on the sameground at certain intervals is of benefit. In this context, the functionality of TDT with great potential has deep-rooted geopolitical foundations.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); International business diplomacy; Non-market strategy; Global institutional governance regime; Practice theory; Institutional governance level; Rule formality; STRATEGY-AS-PRACTICE; CORPORATE DIPLOMACY; PRIVATE REGULATION; INTEGRATED STRATEGY; GLOBAL GOVERNANCE; TRADE-POLICY; MODEL; LEGITIMACY; GOVERNMENT; MULTINATIONALS